STAGES OF THE CULTURE ORGANIZATION DEVELOPMENT: AXIOLOGICAL ANALYSIS - S. I. Tsareva (Дискурс)
The article considers the organization culture as a complex self-developing system that has its own life cycle and developmental features associated with passing of life cycle stages of the organization. Accordingly, the stages that the culture of the organization passes in the process of its development are designated and analyzed in detail. Various points of view on the process under consideration are presented by specialists dealing with this subject. Particular attention is paid to the analysis of the point of view, according to which the culture of the organization passes in its development two stages - the stage of organizational culture and the stage of corporate culture. Organizational and corporate culture is viewed from the standpoint of axiological analysis as relatively independent phenomena: the phenomenon of organizational culture arises in an industrial society, corporate culture as a phenomenon of a modern postindustrial (information) society.